Variability in Urinary Nicotine Exposure Biomarker Levels Between Waves 1 (2013–2014) and 2 (2014–2015) in the Population Assessment of Tobacco and Health Study. Issue 4 (25th March 2022) - Ashley, David L; Zhu, Wanzhe; Wang, Lanqing; Sosnoff, Connie; Feng, Jun; Del Valle-Pinero, Arseima Y; Cheng, Yu-Ching; Chang, Cindy M; van Bemmel, Dana; Borek, Nicolette; Kimmel, Heather L; Silveira, Marushka L; et al.
Abstract: Introduction: To date, no studies have evaluated the consistency of biomarker levels in people who smoke over a long-time period in real-world conditions with a large number of subjects and included use behavior and measures of nicotine metabolism. We evaluated the variability of biomarkers of nicotine exposure over approximately a 1-year period in people who exclusively smoke cigarettes, including intensity and recency of use and brand switching to assess impact on understanding associations with product characteristics. Aims and Methods: Multivariate regression analysis of longitudinal repeated measures of urinary biomarkers of nicotine exposure from 916 adults in the Population Assessment of Tobacco and Health (PATH) Study with demographic characteristics and use behavior variables. Intraclass correlation coefficients (ICCs) were calculated to examine individual variation of nicotine biomarkers and the uncertainty of repeat measures at two time points (Waves 1 and 2). Results: Age, race, and urinary creatinine were significant covariates of urinary cotinine. When including use behavior, recency, and intensity of use were highly significant and variance decreased to a higher extent between than within subjects. The ICC for urinary cotinine decreased from 0.7530 with no use behavior variables in the model to 0.5763 when included. Similar results were found for total nicotine equivalents. Conclusions: Urinary nicotine biomarkers in the PATH Study showed good consistency between Waves 1 and 2. Use behavior measures such as time since last smoked a cigarette and number of cigarettes smoked in the past 30 days are important to include when assessing factors that may influence biomarker concentrations. Implications: The results of this study show that the consistency of the nicotine biomarkers cotinine and total nicotine equivalents in spot urine samples from Waves 1 to 2 of the PATH Study is high enough that these data are useful to evaluate the association of cigarette characteristics with biomarkers of exposure under real-world use conditions.